Spotlight on the Clinical Development, Inventions, and Prospects of the Alzheimer’s Disease Vaccines - Imran, Dr. Mohd (Asian Journal of Pharmaceutics (AJP), 2024)
Alzheimer’s disease (AD) is a degenerative neurological illness. AD causes severe morbidity and expensive healthcare. Although medicines are intended to control symptoms, there is currently no cure for AD or way to stop its development. The conception of vaccines is becoming recognized as a possible tactic. The objective of this review article is to highlight the vaccines under development for AD and inventions related to AD vaccines. The literature for this article was searched on PubMed, reliable websites (United States Food and Drug Administration, innovator companies, clinicaltrial.gov), and patent databases utilizing various keywords belonging to AD vaccines. The literature reveals that many vaccines (ACI-24.060, ACI-35.030_JNJ-2056. ALZN-002, AV-1959D, GV1001, and UB-311) are under development for AD. These vaccines act on different targets (Amyloid-beta, Tau protein, DNA-based antigens, and telomerase reverse transcriptase). The patent search is suggestive for various foreseeable inventions (personalized vaccine; Tau and Amyloid co-targeting; combination therapies; hybrid vaccines, and patient-compliant vaccine delivery methods). The development of AD vaccines represents a promising frontier in addressing one of the most challenging neurodegenerative disorders. As research progresses, AD vaccines could play a crucial role in transforming treatment paradigms, offering new avenues for prevention, and potentially moving us closer to a cure.